Physical fitness and activities of daily living in primary ciliary dyskinesia: A retrospective study. Issue 1 (19th April 2022) - Sonbahar‐Ulu, Hazal; Cakmak, Aslihan; Inal‐Ince, Deniz; Vardar‐Yagli, Naciye; Yatar, Ilker; Calik‐Kutukcu, Ebru; Saglam, Melda; Tekerlek, Haluk; Bozdemir‐Ozel, Cemile; Arikan, Hulya; Emiralioglu, Nagehan; Ozcelik, Ugur
Abstract: Background: Primary ciliary dyskinesia (PCD) is a rare, hereditary, autosomal recessive disorder characterized by recurrent upper and lower respiratory tract infections. This study aimed to compare pulmonary function, respiratory muscle strength, exercise capacity, physical fitness, and activities of daily living (ADLs) retrospectively between patients with PCD and healthy controls. Methods: Data from 20 patients with PCD and 20 matched, healthy counterparts recorded between July 2015 and January 2017 were analyzed. The data evaluated and recorded included pulmonary function using a portable spirometer, respiratory muscle strength (using a mouth pressure device, exercise capacity using the incremental shuttle walk test, ), physical fitness (using the Munich Fitness Test), and ADLs (using the Glittre ADL test). Results: Pulmonary function, respiratory muscle strength, incremental shuttle walk test scores (all parameters), and total Munich Fitness Test scores were lower in the PCD group relative to controls ( P < 0.05). The duration to complete the Glittre ADL test was higher in PCD patients than in healthy subjects ( P < 0.05). Conclusions: Pulmonary function, respiratory muscle strength, exercise capacity, physical fitness, and ADL were affected by PCD. Thus, pulmonary rehabilitation regimens should be tailored according to these impacts.